2022
DOI: 10.1177/10547738221086984
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acupuncture and or Moxibustion for Managing Primary Dysmenorrhea: A Systematic Review and Meta-Analysis

Abstract: Acupuncture and moxibustion have been accepted as add-on options for primary dysmenorrhea (PD); however, the clinical evidence is still inadequate. We searched AMED, CENTRAL, EMBASE, PubMed, Web of Science, CBM, CNKI, VIP, Wangfang database, ANZCTR, ClinicalTrials.gov, and the WHO ICTRP, from their inception to February 2021. The pooled analysis of 13 RCTs with 675 participants for VAS showed that acupuncture and moxibustion were more effective in managing PD than the control group with the MD of −1.93 (95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Reported adverse outcomes like little bleeding, hematoma, bruises, dizziness or fainting are mild and harmless. Serious side effects were not observed [10,13]. To summarize, acupuncture could potentially be an effective and safe method of treatment for PD, but more thorough clinical research and better quality of evidence are needed to prove it [1,2,10].…”
Section: Acupuncturementioning
confidence: 97%
See 1 more Smart Citation
“…Reported adverse outcomes like little bleeding, hematoma, bruises, dizziness or fainting are mild and harmless. Serious side effects were not observed [10,13]. To summarize, acupuncture could potentially be an effective and safe method of treatment for PD, but more thorough clinical research and better quality of evidence are needed to prove it [1,2,10].…”
Section: Acupuncturementioning
confidence: 97%
“…However, a recent meta-analysis shows that acupuncture can remarkably reduce pain and may be an effective option for PD, but the level of certainty was moderate [13]. Reported adverse outcomes like little bleeding, hematoma, bruises, dizziness or fainting are mild and harmless.…”
Section: Acupuncturementioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 1, 2024. ; https://doi.org/10.1101/2024.03.30.24305112 doi: medRxiv preprint acupuncture therapy, 34 acupressure, 35 aromatherapy, 17 exercise, 23 TENS, 36 physiotherapy, 37 psychological intervention, 20 manual therapy, 38 moxibustion, 39 nutritional therapy, 25 non-invasive brain stimulation, used as treatment will be included. 40 No restrictions will be placed on the intervention timing (pre-menstrual, menstrual period, post-menstrual), courses, or delivery form (researchers, self, or device).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Acupuncture is commonly used as an alternative treatment for PD because of its efficacy and safety [ 6 ]. Available studies have indicated that acupuncture treats PD by regulating endocrine and analgesic substances, modulating immune-inflammatory responses, improving uterine blood flow, and reducing oxidative stress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%